The correlation analysis between Normalized Wall Index and cerebral perfusion in patients with Mild Carotid Artery Stenosis under 3.0T MRI - Yonggang Cai; Shouming Chen; Tongyu Shang; Binze Han; Lei Zhang; Changyan Xu; Zhibin He; Ting Yin (BMC Medical Imaging)
Abstract Background To explore the relationship between Normalized Wall Index (NWI) and Magnetic Resonance Perfusion Imaging Parameters in Patients with Mild Carotid Artery Stenosis. Methods Initially, an analysis was conducted on 40 patients from our institution, and we identified through ultrasonographic examinations conducted between July 2021 and August 2022. These patients exhibited carotid artery plaques with mild luminal narrowing (with stenosis rates ranging from 20 to 50%, following the criteria of the North American Symptomatic Carotid Endarterectomy Trial, NASCET). All cases underwent high-resolution magnetic resonance imaging (MRI) of the carotid arteries and cerebral perfusion assessments using 3.0T MRI during the specified timeframe. Based on whether the cerebral hemisphere in the carotid artery supply region had experienced ischemic events, including Transient Ischemic Attacks (TIAs), patients were categorized into symptomatic and asymptomatic groups. Subsequently, the Normalized Wall Index (NWI) of the carotid arteries and the area of abnormal perfusion on the same side of the brain were calculated for each group. Results In the symptomatic group, all patients exhibited perfusion abnormalities in the internal carotid artery supply region, whereas only some patients in the asymptomatic group showed such abnormalities. The NWI of plaques in the symptomatic group was significantly higher than that in the asymptomatic group (P < 0.05). Conclusion The range of prolongation in mean transit time (MTT) and time to peak (TTP) in patients with perfusion abnormalities was positively correlated with NWI and stenosis rates. The association with NWI was more pronounced and statistically significant (P < 0.05).